Inelastic J/[psi] photoproduction in electron-proton collisions at HERA - Yip, T; Yip, Timothy C.Y. (1996)
﻿ The development of a neural network based electron finder designed for the ZEUS calorimeter is described. A study of elastic and inelastic J/ψ meson production in electron-proton collisions at HERA using the ZEUS detector is presented. During the 1993 and 1994 running periods, the ZEUS detector collected ~ 500 nb-1 and ~ 3 pb-1 of data respectively. The direct inelastic J/ψ photoproduction cross-section is measured for both running periods and an attempt is made to extract the gluon density inside the proton using the 1994 inelastic J/ψ sample.